Peran Kepala Desa Dalam Pelaksanaan Pembangunan Menurut Undang-Undang Desa dan Fiqh Siyasah; Studi Kasus Desa Mekarjati Kecamatan Haurgeulis Kabupaten Indramayu - Susanto Susanto; Abdur Rahim (JOURNAL of LEGAL RESEARCH, 2021)
The performance of a village head as head of village government must be able to carry out its main duties, namely leading and coordinating the village administration in implementing village development. The role of the village head is one aspect that stands out and affects the success of village development. The village head is assisted by village officials, as an element of village government administration. The formulation of the problem in this research is "What is the Role of the Village Head in the Implementation of Development in Mekarjati Village, Haurgeulis Subdistrict, Indramayu Regency" and "How the Siyasah Fiqh Review and the Village Law on the Role of the Village Head in Implementing Development in Mekarjati Village". The purpose of this research is "To know the role of the village head in the implementation of village development, and" to know the Siyasah Fiqh Overview of the role of the village head in the implementation of village development." This type of research is classified as field research (field research), which is descriptive analysis, namely research that tells and describes data originating from primary data through interviews, observations and reports in the form of documents and secondary data by conducting library research. Based on the research results, it can be concluded that the role of the Mekarjati Village Head, in the implementation of village development in general, there are still some that are not optimal. It can be seen that there are still some developments that have not been carried out optimally, such as the development of education and environmental security systems (Siskamling).Keywords: Role, Village Head, Implementation, Development, Village Law, Fiqh Siyasah